IMMUNE STATUS OF CHILDREN WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (American Journal of Pedagogical and Educational Research, 2024)
In the development of chronic obstructive pulmonary disease (COPD) in children, the child’s premorbid background and the state of the body’s general reactivity play an important role. Among the endogenous factors that determine the likelihood of developing this disease, great importance is attached to immunological processes. We examined 100 sick children with COPD who were undergoing inpatient treatment in the children's department of the SamMI clinic No. 1. Group I consisted of 30 patients aged 3-7 years (with bronchial deformation - 24 patients; with bronchiectasis - 6), group II - 70 patients aged 8-15 years (with bronchial deformation - 46 patients; with bronchiectasis - 24 ). The conducted studies confirm the significant pathogenetic significance of immunological deficiency in COPD in children and indicate the need for its correction.